FEATURES OF THE COURSE OF TUBERCULOSIS OF THE RESPIRATORY SYSTEM IN PATIENTS OF DIFFERENT AGE GROUPS - Turdibekov, Khusan Ibragimovich; Khusanovich, Ibragimov Sanjarbek ; Sakhobzhonovna, Zhurabaeva Gulira'no (Journal of Medical Genetics and Clinical Biology, 2024)
A comparative analysis of the results of examination of young and elderly patients with respiratory tuberculosis is presented. Statistical data on the forms of tuberculosis, clinical pictures, clinical and laboratory data among this category of patients were obtained. Tuberculosis in adolescents is more often detected during preventive examinations and contact examinations, and among adult youth — when seeking medical help. Unilateral limited processes without destruction or with small cavities, without isolation of mycobacterium tuberculosis, are more typical for adolescents. In adults, tuberculosis is more often accompanied by pulmonary symptoms, intoxication, and complications. It is recommended to take into account the established features when working with these age groups at the stage of the general treatment network for the timely active detection of tuberculosis patients